Baptists in America : a history - Kidd, Thomas S.; Hankins, Barry, 1956- (Oxford ; New York : Oxford University Press, 2015)
The Puritans hounded the Baptists out of Massachusetts Bay Colony. Four hundred years later, Baptists are the second-largest religious group in America, and their influence matches their numbers. Yet the historical legacy, and the inherently fractured nature of their faith, makes Baptists ever wary of threats from within as well as without. Kidd and Hankins, both practicing Baptists, weave the threads of Baptist history alongside those of American history to show how one religious denomination was transformed from persecuted minority into a leading actor on the national stage, with profound implications for American society and culture.
Colonial outlaws -- The Great Awakening -- Baptists and the American revolution -- Baptists and disestablishment -- Baptists and the great revival -- Baptists and slavery -- Slavery, schism, and war -- Black Baptists in Babylon -- White Baptists and the American mainstream -- Baptist schism in the early twentieth century -- Insiders and outsiders at mid-twentieth century -- Baptists and the civil rights movement -- Schism in Zion: the Southern Baptist controversy -- Conclusion.
Includes bibliographical references and index.
Keywords: Baptists -- United States -- History; United States -- Church history